Spatial organization of the ions at the free surface of imidazolium-based ionic liquids - Tóth Ugyonka, Helga; Hantal, György; Szilágyi, István; Idrissi, Abdenacer; Jorge, Miguel; Jedlovszky, Pál (Journal of Colloid and Interface Science, 2024)
Hypothesis: Experimental information on the molecular scale structure of ionic liquid interfaces is controversial, giving rise to two competing scenarios, namely the double layer-like and “chessboard”-like structures. This issue can be resolved by computer simulation methods, at least for the underlying molecular model. Systematically changing the anion type can elucidate the relative roles of electrostatic interactions, hydrophobic (or, strictly speaking, apolar) effects and steric restrictions on the interfacial properties. Simulations: Molecular dynamics simulation is combined with intrinsic analysis methods both at the molecular and atomic levels, supplemented by Voronoi analysis of self-association. Findings: We see no evidence for the existence of a double-layer-type arrangement of the ions, or for their self-association at the surface of the liquid. Instead, our results show that cation chains associate into apolar domains that protrude into the vapour phase, while charged groups form domains that are embedded in this apolar environment at the surface. However, the apolar chains largely obscure the cation groups, to which they are bound, while the smaller and more mobile anions can more easily access the free surface, leading to a somewhat counterintuitive net excess of negative charge at the interface. Importantly, this excess charge could only be identified by applying intrinsic analysis.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Computer simulation; Imidazolium-based liquids; Interfacial structure; Intrinsic surface; Ionic liquids; Liquid surface; Self-association